2008
DOI: 10.1007/s12275-008-0118-y
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter soli sp. nov., isolated from forest soil

Abstract: A non-motile and rod shaped bacterium, designated strain B1(T), was isolated from forest soil at Mt. Baekwoon, Republic of Korea. Cells were Gram-negative, catalase-positive, and oxidase-negative. The major fatty acids were 9-octadecenoic acid (C(18:1) omega9c; 42%) and hexadecanoic acid (C(16:0); 25.9%) and summed feature 3 (comprising iso-C(15:0) 2-OH and/or C(16:1) omega7c; 10.0%). The DNA G+C content was 44.1 mol%. A phylogenetic tree based on 16S rRNA gene sequences showed that strain B1(T) formed a linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 27 publications
0
35
0
1
Order By: Relevance
“…S1 in the supplemental material.) Because A. soli is genetically distant from the ACB complex (72,73), it was used to root the tree. Similar to prior studies, our results showed that A. nosocomialis diverges first from the A. baumannii clade, followed by A. pittii (20).…”
Section: Resultsmentioning
confidence: 99%
“…S1 in the supplemental material.) Because A. soli is genetically distant from the ACB complex (72,73), it was used to root the tree. Similar to prior studies, our results showed that A. nosocomialis diverges first from the A. baumannii clade, followed by A. pittii (20).…”
Section: Resultsmentioning
confidence: 99%
“…Species identifications of the isolates were initiated by partial sequencing of the rpoB gene (zone 1) according to the method of Karah et al (3,4). PCR products were purified with a QIAquick PCR purification kit (Qiagen, Hilden, Germany), followed by DNA sequencing using an ABI BigDye Terminator v3.1 cycle sequencing kit (Applied Biosystems, Foster City, CA, USA) and an ABI3730xl analyzer (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…are almost identical to those of each other, accurate identification at the species level is difficult with routine laboratory methods. Recently, some molecular techniques have been reported for identifying isolates at the species level, such as sequencing the 16S rRNA gene, the gyrB gene, the recA gene, or the RNA polymerase ␤-subunit (rpoB) gene (4)(5)(6)(7). These molecular methods recently led to progress in the accurate identification of Acinetobacter species.…”
mentioning
confidence: 99%
“…Acinetobacter soli was first isolated from the forest soil in Korea, 2007. Since then, the bloodstream infection outbreak caused by this species in neonatal intensive care unit (ICU) has also been reported in Korea, 2011 and the first carbapenem-resistant isolates were detected in Japan, 2012 [5][6][7]. However, carbapenemresistant and bla NDM-1 producing A. soli has not yet been reported in China.…”
mentioning
confidence: 99%